5,5′-Diamino-BIPHEP ligands bearing small selector units for non-covalent binding of chiral analytes in solution - Storch, Golo; Siebert, Max; Rominger, Frank; Trapp, Oliver (Chemical communications, 2015)
A dynamic axially chiral BIPHEP-ligand with 3,5-dichlorobenzoyl amide selector units for non-covalent binding of phenylalanine derivatives has been developed. Interaction studies in solution were performed with rhodium(I) complexes under exclusion of the metal being involved in binding. (Rax, SPhe) and (Sax, SPhe) adducts were observed as significantly separated species in NMR spectroscopy.